10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundClinical frailty is an emerging health problem and a risk factor for venous disease and its adverse outcomes. This review and meta-analysis will determine the association of frailty in the development of venous diseases and related adverse outcomes.Materials and methodsA literature review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Searches were done in PubMed and Embase, from 1 January 2007 to 1 January 2025. Articles that were not related to frailty and venous disease were excluded. References from review papers were further screened following the same inclusion and exclusion criteria. R studio was used for the meta-analysis of the studies on non-postoperative venous thromboembolism (VTE) and pulmonary embolism (PE).ResultsA total of 1338 articles were retrieved, and 72 papers, involving 6,407,901 patients, were included in the final review. Sixty-one studies assessed frailty and postoperative complications, and 65% reported that frail patients had a higher risk of postoperative VTE (p < 0.05). Spinal, neurosurgical, abdominal, and orthopaedic patients exhibited the highest rates across surgical specialties. Meta-analysis of six studies demonstrated that frailty was associated with an increased risk of non-postoperative VTE (OR 1.91, 95% CI 1.15-3.18, p = 0.012). Three papers showed that high frailty risk was associated with greater odds of mortality in patients with PE (Pooled OR 9.95, 95% CI 6.32-15.67, p < 0.0001). Of the remaining two studies, one found that frail patients were more likely to have ulcer recurrence than non-frail patients (p < 0.001). The other reported that frail patients had a higher risk of varicose veins than non-frail patients (p = 0.01).ConclusionClinical frailty is associated with an increased risk of VTE and adverse outcomes in venous disease, although the certainty of evidence is limited by substantial heterogeneity and methodological differences among studies.